Zooplankton size composition and production just after drastic ice coverage changes in the northern Bering Sea assessed via ZooScan - Kumagai, Shino; Matsuno, Kohei; Yamaguchi, Atsushi (Frontiers in Marine Science, 2023)
Drastic environmental changes were noted in the northern Bering Sea in 2018. A reduction in sea ice affected several trophic levels within the ecosystem; this resulted in delayed phytoplankton blooms, the northward shifting of fish stocks, and a decrease in the number of seabirds. Changes in the community composition of zooplankton were reported in 2022, but changes in zooplankton interactions and production have not been reported to date. Therefore, this study examined predator-prey interaction, secondary production, and prey availability for fish to understand the effect of early sea ice melt. Zooplankton size data were estimated from the size spectra obtained using ZooScan based on samples collected in 2017 and 2018. A cluster analysis based on biovolume showed that the zooplankton community could be divided into three groups (Y2017N, Y2017S, Y2018). Y2017N, characterized by low abundance, biomass, and production, Y2017S, characterized by high biovolume and production, which contributed with Calanus spp., and Y2018, characterized by low biovolume but high production, contributed with small copepods, and Bivalvia. In 2017, the highest biovolume group was observed south of St. Lawrence Island, and it was dominated by Calanus spp. and Chaetognatha. Normalized size spectra of this group showed the highest secondary production with present predator-prey interactions, suggesting that the area provides high prey availability for fish larvae and juveniles. In contrast, small copepods and bivalve larvae were dominant in this area in 2018, which contain less carbons and energy, suggesting the prevalence of low-nutrient foods in this year in relation to early sea ice melt.